Factors Associated with HIV Related Stigma among College Students in the Midwest - Caroline Kingori; Mavis Adwoa Nkansah; Zelalem Haile; Kay-Anne Darlington; Tania Basta (AIMS Press, 2017)
In general, U.S. college students have low perceived susceptibility of acquiring HIV infection while 15-25 percent of youth have had negative perceptions towards HIV positive individuals. Factors associated with HIV stigma among college students were examined in a convenience sample of 200 students. Descriptive and inferential statistics were utilized to summarize the data. Only four percent of participants responded correctly to HIV transmission knowledge items. HIV transmission knowledge scores were significantly higher for participants who were single with partner and those who resided outside university residential dorms (p < 0.05). There was a significant negative correlation between composite HIV knowledge scores and stigma scores r = −0.18 (p < 0.05). After adjusting for confounders, a marginal significant negative linear relationship emerged (β = −0.09, p = 0.06) between HIV knowledge and stigma. HIV prevention education among college students needs to be addressed with nuance to minimize HIV knowledge gaps, stigma and student risk perception that impacts HIV prevention and stigma against those living with HIV.